การเพิ่มความพร้อมของผู้ป่วยในการส่งปรึกษาเพื่อผ่าตัดเจาะคอโดยใช้แบบฟอร์มปรึกษาเจาะคอแบบรายการตรวจสอบในโรงพยาบาลมหาราชนครราชสีมา: Checklist Tracheostomy Consultation Form Increase Promptness of Patients at Consultation for Tracheostomy in Maharat Nakornratchasima Hospital - Parapiboon, Watanyu; Rotjanasiriphong, Chutima (Asian Health, Science and Technology Reports, 2018)
การเตรียมความพร้อมของผู้ป่วยเมื่อส่งปรึกษาเพื่อผ่าตัดเจาะคอมีความสำคัญ อย่างไรก็ตามยังอุบัติการณ์การเตรียมผู้ป่วยไม่พร้อมขณะส่งปรึกษาเพื่อผ่าตัดเจาะคอสูง จึงได้พัฒนาแบบฟอร์มปรึกษาเจาะคอแบบรายการตรวจสอบและนำไปใช้ จุดประสงค์ของการศึกษาเพื่อเปรียบเทียบอุบัติการณ์ความไม่พร้อมขณะส่งปรึกษาเพื่อผ่าตัดเจาะคอในช่วงก่อนและหลังการใช้แบบฟอร์มปรึกษาเจาะคอแบบรายการตรวจสอบ โดยเก็บข้อมูล 176 การปรึกษาในช่วง 6 เดือนในโรงพยาบาลระดับตติยภูมิ อุบัติการณ์ความไม่พร้อมขณะส่งปรึกษาผ่าตัดเจาะคอ ร้อยละ 32.9 ในช่วงก่อนและ ร้อยละ 17.5 ในช่วงหลังใช้แบบฟอร์มปรึกษาเจาะคอแบบรายการตรวจสอบ โดยอัตราเสี่ยงสัมพัทธ์ของความไม่พร้อมลดลง 0.81 นอกจากนี้แพทย์ผู้ใช้แบบฟอร์มปรึกษาส่วนใหญ่มีความพึงพอใจและยินดีที่จะใช้ต่อไป การใช้แบบฟอร์มปรึกษาเจาะคอแบบรายการตรวจสอบลดความไม่พร้อมของผู้ป่วยขณะส่งปรึกษาเพื่อผ่าตัดเจาะคอลงได้ Background: The preparation of patients before tracheostomy was important. However, the incidence of unprompted patients at consultation for tracheostomy is stilled high. In order to increase patients safety and promptness for tracheostomy. Checklist tracheostomy consultation form (CTCF) has been developed and applied. CTCF use the checklist tool to remind the physician. This study aims to evaluate the effectiveness of CTCF. Methods: We conducted a prospective cohort study with historical controls of 176 consultation in inpatient department for tracheostomy in tertiary care hospital in Thailand during 6 months period. Incidence of unprompted patients at consultation for tracheostomy were compared in era before and after using CTCF. Comparison were analyzed with Chi-square and relative risk calculation. Results: 85 patients were in era before using CTCF (Before group) and 91 patients were in era after using CTCF (After group). In before group, the incidence of unprompted patients at consultation for tracheostomy were 32.9%. Compare to those in the after group, the incidence of unprompted patients at consultation for tracheostomy was 17.5%. CTCF reduced risk of unprompted patients at consultation for tracheostomy significantly (RR 0.81, 95%CI 0.68 - 0.97). Moreover, most of physician who used CTCF were satisfied and trended to continue using CTCF. Conclusions: Using checklist tracheostomy consultation form (CTCF) reduced the incidence of unprompted patients at consultation for tracheostomy and may remind the physicians in preparing patients before tracheostomy.